Simulation studies on microwave-assisted pyrolysis of biomass for bioenergy production with special attention on waveguide number and location - Mohd Mokhta Z.; Ong M.Y.; Salman B.; Nomanbhay S.; Salleh S.F.; Chew K.W.; Show P.-L.; Chen W.-H. (Elsevier Ltd, 2023)
Bioconversion; Electric fields; Electromagnetic field effects; Electromagnetic fields; Energy efficiency; Microwave heating; Microwaves; Pyrolysis; Waveguides; Bio-energy; Bioenergy productions; Conventional heating; Electric field distributions; Influential factors; Maximum temperature; Microwave-assisted pyrolysis; Simulation; Biomass; bioenergy; bioreactor; computer simulation; electric field; electromagnetic field; heating; microwave radiation; pyrolysis; software